Insight Into Nanoliposomes as Smart Nanocarriers for Greening the Twenty-First Century Biomedical Settings - Aguilar-Pérez, K. M.; Avilés-Castrillo, J. I.; Medina, Dora I.; Parra-Saldivar, Roberto; Iqbal, Hafiz M. N. (Frontiers in Bioengineering and Biotechnology, 2020)
The necessity to develop more efficient, biocompatible, patient compliance, and safer treatments in biomedical settings is receiving special attention with the use of nanotechnology as a potential platform to design new drug delivery systems. Despite the broad range of novel nanocarrier systems in drug delivery, lack of biocompatibility, poor penetration, low entrapment efficiency, and toxicity are some of the significant challenges that remain to address. Such practices are even more demanding when bioactive agents are intended to be loaded on a nanocarrier system, especially for topical treatment purposes. For the previous reasons, the search for more efficient nano-vesicular systems with a high biocompatibility index and controlled releases such as nanoliposomes has increased considerably in the past few decades. Owing to the stratum corneum layer barrier of the skin, the in-practice conventional/conformist drug delivery methods are inefficient, and the effect of the administered therapeutic cues is limited. The current advancement at the nanoscale has transformed the drug delivery sector. With particular reference, nanoliposomes, as robust nanocarriers, are becoming popular for drug delivery applications because of safety, patient compliance, and quick action. Herein, we reviewed state-of-the-art nanoliposomes as a smart and sophisticated drug delivery approach. Following a brief introduction, the drug delivery mechanism of nanoliposomes is discussed with suitable examples for the treatment of numerous diseases with a brief emphasis on fungal infections. The latter half of the work is focused on the applied perspective and clinical translation of nanoliposomes. Furthermore, a detailed overview of clinical applications and future perspectives has been included in this review.